Marketization and crime in contemporary China: Puzzles for criminological theorizing*. Issue 2 (8th January 2022) - Messner, Steven F.
Abstract: The purpose of my Sutherland Address is to explore the potential utility of elaborating and adapting the analytic framework of Institutional Anomie Theory (IAT) to account for the macro‐social dynamics of crime in contemporary China. To do so, I situate the institutional dynamics of crime in China in comparative historical context and put forth a newly adapted formulation of IAT. I then illustrate the ways in which this adapted formulation of IAT can enhance the coherence of a rich body of research on crime in China by incorporating some of the empirical findings and insightful interpretations within an overarching theoretical framework. In addition, interrogating the applicability of IAT to the Chinese context draws attention to important gaps in the theory, thereby facilitating its further elaboration as well as promoting the development of general macro‐social theory in criminology.